Antiretroviral Therapy for HIV‐1–Infected Children in Haiti - Erik George; Francine Noël; Gyrlande Bois; Rachelle Cassagnol; Louise Estavien; Patricia De Matteis Rouzier; Rose Irène Verdier; Warren D. Johnson; Jean W. Pape; Daniel W. Fitzgerald; Peter F. Wright (2007)
Data are limited about the effectiveness of pediatric antiretroviral therapy (ART) in low-income countries.We report the outcomes of consecutively treating 236 human immunodeficiency virus type 1 (HIV-1)-infected treatment-naive children with triple ART in Port-au-Prince, Haiti, between 1 May 2003 and 30 April 2006.Kaplan-Meier survival analysis at follow-up demonstrated that 191 children (81%) remained in care, 21 (9%) were dead, and 24 (10%) were lost to follow-up. Independent baseline predictors of mortality were age <18 months, CD4(+) T cell percentage < or =5%, and weight-for-age Z score (WAZ) less than -3. Twelve months into ART, 56% of tested subjects had undetectable HIV-1 RNA loads. Median CD4(+) T cell percentages at 12 months increased by 15%, 11%, and 5% in children with baseline percentages of < or =5%, 6%-24%, and > or =25%, respectively (P<.01). The median WAZ at 12 months increased by 1.0, 0.6, and 0.2 in children with baseline WAZ less than -2, -2 to -1.1, and -1 or more, respectively (P<.01).With continuous donor support, trained providers, and the availability of pediatric antiretroviral drug formulations, it proved feasible to deliver pediatric ART in Haiti. The effectiveness of this program should encourage efforts to make ART available for HIV-infected children in poor countries.